"Frontline Nurses Readiness": How Did Nurses Learn About Nursing Care During the Pandemic in Indonesia? - Riski Amalia; Nurul Hadi; Nani Safuni; Irfanita Nurhidayah; Nurhasanah; Yuni Arnita (Asian Journal of Public Health and Nursing, 2024)
Background: The COVID-19 pandemic has caused adjustments in health services and hospital procedures, particularly in the provision of nursing care to patients. The shift of health care during the COVID-19 pandemic has had both beneficial and bad consequences, including the dynamics, problems, and impediments that nurses encounter.   Methods: This descriptive phenomenological study investigated nurses' readiness to offer nursing care during the COVID-19 pandemic in Indonesia. Semi-structured interviews were performed with 13 nurse participants in a teaching hospital in the province of Aceh, Indonesia. The Collaizzi method, consisting of seven steps, was used to examine qualitative data.   Results: The study identified four major themes: 1) modifying health services during a pandemic; 2) coping mechanisms for nurses dealing with a pandemic; 3) barriers to providing nursing care during a pandemic; and 4) making wish come true during a pandemic.   Conclusion: Nurses' experience enhancing health care during the COVID-19 pandemic requires more improvement, integration, and holistic thinking. Nonetheless, they must treat patients even when their situations are not favourable. The proposed research should address the significance of optimizing care during a pandemic, such as nurse safety and security, government measures to limit COVID-19 in nursing services, and nurses' effective pandemic methods in Indonesia